Image Processing Techniques on Radiological Images of Human Lungs Effected by COVID-19 - A.M. Sirisha; P. Venkateswararao (Society of Visual Informatics, 2020)
The wide spread of COVID-19 all over the world inspires every human to know and visualize its effect on human body. As Â Â COVID-19 effects the human lungs here a number of radiological images of human lungs are analysed using an image processing technique called Threshold Segmentation. A significant difference is observed between healthy lung images and COVID-19 effected lung images.